Reacting to ambiguous messages: An experimental analysis - Christian Kellner; Mark Thordal-Le Quement; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
Ambiguous language is ubiquitous and often deliberate. Recent theoretical work (Beauchêne et al., 2019; Bose and Renou, 2014; Kellner and Le Quement, 2018) has shown how language ambiguation can improve outcomes by mitigating conflict of interest. Our experiment finds a significant effect of language ambiguation on subjects who are competent Bayesian updaters. For both ambiguity averse and neutral subjects within this population, one significant channel is behavioral in nature (anchoring). For ambiguity averse subjects, another channel of similar magnitude is hedging motivated by the desire to reduce ambiguity. This channel is absent in the case of ambiguity neutral subjects.
Keywords: C91; D01; D81; 330; Ambiguity aversion; Communication; Persuasion; Laboratory experiment